2014
DOI: 10.5123/s2176-62232014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição ao conhecimento do escorpionismo e do escorpião Tityus obscurus Gervais, 1843 (Scorpiones, Buthidae) de duas regiões distintas no Estado do Pará na Amazônia brasileira*

Abstract: Introdução: O Tityus obscurus Gervais, 1843 (Scorpiones, Buthidae), sinônimo sênior de T. paraensis Kraepelin, 1896 e T. cambridgei Pocock, 1897 tem ampla distribuição na Amazônia brasileira, sendo o de maior importância médica na região e apresenta manifestação clínica diversificada, dependendo da região. Objetivo: Contribuir para o conhecimento da diversidade do escorpionismo e do escorpião T. obscurus na Amazônia brasileira. Metodologia: Descrever, analisar e comparar os aspectos clínico-epidemiológicos do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 0 publications
2
1
0
16
Order By: Relevance
“…This study demonstrated that 65.2% of scorpionism events were classified as light; similar results were obtained in Belém, Pará, Brazil (8) . Serotherapy with anti-scorpion venom was administered in 57.7% of the cases, which is a higher rate than that observed in other localities where only 2.1-7.5% of injured patients were administered anti-venom (7) (sometimes unnecessarily according to the Ministry of Health (14) ).…”
Section: Species Involved With Scorpionism In Amazonassupporting
confidence: 86%
See 1 more Smart Citation
“…This study demonstrated that 65.2% of scorpionism events were classified as light; similar results were obtained in Belém, Pará, Brazil (8) . Serotherapy with anti-scorpion venom was administered in 57.7% of the cases, which is a higher rate than that observed in other localities where only 2.1-7.5% of injured patients were administered anti-venom (7) (sometimes unnecessarily according to the Ministry of Health (14) ).…”
Section: Species Involved With Scorpionism In Amazonassupporting
confidence: 86%
“…The rate of stinging incidents leading to death was of 0.03 per 100,000 inhabitants, below the national average of approximately 0.04 per 100,000 inhabitants; however, this rate was similar to that found in the State of Pará (8) .…”
Section: Species Involved With Scorpionism In Amazonassupporting
confidence: 63%
“…A fauna escorpiônica constitui-se de 18 famílias, 151 gêneros e 1.947 espécies (CHIPPAUX;GOYFFON, 2008 Tityus bahiensis, na região Sudeste; e o Tityus obscurus, na região Norte (BRASIL, 2009; CHIPPAUX; GOYFFON, 2008;TORREZ et al, 2014). Na Amazônia, as espécies mais encontradas são o T. obscurus (também denominado T.cambridgei e T. paraenses), o T. silvestris e o T. metuendus (PARDAL et al,2003;PARDAL et al,2014). A espécie T.…”
Section: Apêndice I -Termounclassified
“…Estes canais são responsáveis por gerar sinais elétricos para a formação e propagação do potencial de ação, necessários para a condução do impulso nervoso, batimentos cardíacos, secreção hormonal, função renal e ativação de células do sistema imune (CATTERAL et al, 2007 (GUERRERO-VARGAS et al, 2012;PARDAL et al, 2014).…”
Section: Mecanismo De Ação Do Venenounclassified
See 1 more Smart Citation